Viral–Bacterial Interactions in Acute Otitis Media - Marom, Tal; Nokso-Koivisto, Johanna; Chonmaitree, Tasnee (Current allergy and asthma reports, 2012)
Acute otitis media (AOM) is a polymicrobial disease, which usually occurs as a complication of viral upper respiratory tract infection (URI). While respiratory viruses alone may cause viral AOM, they increase the risk of bacterial middle ear infection and worsen clinical outcomes of bacterial AOM. URI viruses alter Eustachian tube (ET) function via decreased mucociliary action, altered mucus secretion and increased expression of inflammatory mediators among other mechanisms. Transient reduction in protective functions of the ET allows colonizing bacteria of the nasopharynx to ascend into the middle ear and cause AOM. Advances in research help us to better understand the host responses to viral URI, the mechanisms of viral–bacterial interactions in the nasopharynx and the development of AOM. In this review, we present current knowledge regarding viral–bacterial interactions in the pathogenesis and clinical course of AOM. We focus on the common respiratory viruses and their established role in AOM.